Epidemiological overview of dengue in Bahia: A decade of data (2014-2023) (Research, Society and Development, 2024)
Dengue is a viral disease that mainly affects tropical and subtropical regions, with Brazil being one of the leading countries in reported cases. In Brazil, the state of Bahia is one of the most affected, being the Northeastern state with the highest number of reported cases, making epidemiological studies in the region relevant, as such an approach is essential for planning effective public control policies. In this context, the present study aims to outline the epidemiological and vulnerability profile for dengue in Bahia. This is a cross-sectional, exploratory study with a quantitative and retrospective approach, conducted between the years 2014 and 2023. The database for the study is derived from the Notifiable Diseases Information System (SINAN), and the data were analyzed using GraphPad Prism. During the analyzed period, 417,515 probable dengue cases were reported in Bahia, with Salvador (52,685) and Itabuna (32,104) leading the notifications. The investigation revealed a higher incidence in female individuals, mixed-race (pardo), aged between 20 and 39 years, and with low educational levels. Additionally, it was observed that the number of notifications in Salvador follows the fluctuations of Bahia during the studied period. In summary, the data reinforce the endemic nature of dengue in Bahia and the need for the creation of public policies targeted at individuals with a higher vulnerability profile.